Single Nucleotide Polymorphisms in the Human Leukocyte Antigen Region Are Associated With Hemagglutination Inhibition Antibody Response to Influenza Vaccine - Zhong, Shuyi; Wei, Hejiang; Li, Mao; Cheng, Yanhui; Wen, Simin; Wang, Dayan; Shu, Yuelong (Frontiers in Genetics, 2022)
Abstract Background: The annual death of seasonal influenza is 290,000-650,000 globally, which can be effectively reduced by influenza vaccination. However, the protective hemagglutination inhibition (HAI) antibody response to influenza vaccine is affected by many factors, among which single nucleotide polymorphisms (SNPs) in human leukocyte antigen (HLA) region can alter the antigen-presenting function of HLA molecule, thus may influence the process of antibody mounting against vaccine antigen. Methods: Healthy subjects of the Han nationality were recruited and received seasonal trivalent influenza vaccine. Paired serum samples collected on and approximately 28 days after vaccination were tested in parallel by HAI assays. HLA alleles related to the immune response to influenza vaccine reported in the previous literature were summarized and 6 corresponding tag SNPs were selected and genotyped using the MassARRAY technology platform. Results: The effects of HLA SNPs on HAI antibody response to influenza vaccine varied with different vaccine antigens. The AA genotype of rs41547618 was correlated with lower A/H1N1 specific antibody titer compared with GG+GA genotype (P=0.007). The TT genotype of rs17885382 was correlated with lower A/H3N2 specific antibody titer compared with CC+CT genotype (P=0.003). In addition, haplotype consisting of rs41542812 - rs17885382 - rs2068205 - rs41547618 - rs6905837 - rs9270299 - CCTGCA was correlated with non-responsiveness to influenza vaccine (OR=2.39, 95%CI=1.02-5.62). Conclusion: HLA SNPs were associated with HAI antibody response to influenza vaccine, which can help better understand the varied responsiveness to influenza vaccine in population.